Effects of ω-3 Polyunsaturated Fatty Acids on Coronary Atherosclerosis and Inflammation: A Systematic Review and Meta-Analysis - Gao, Zheng; Zhang, Dewen; Yan, Xiaocan; Shi, Hekai; Xian, Xiaohui (Frontiers in Cardiovascular Medicine, 2022)
Background and purpose: Multiple guidelines suggest the ω-3 polyunsaturated fatty acids (ω-3 PUFAs) help to prevent major vascular events of CHD, but the data on large trials of ω-3 fatty acids are controversial. We reviewed the available evidence to determine the effect of ω-3 PUFAs on coronary atherosclerosis. Methods and materials: Literatures were from online databases. Random controlled trials or observational studies were acceptable. Quantitative data synthesis was conducted by R version 4.1.2. Each outcome was calculated using standardized mean difference (SMD) in a random effect model. Sensitivity analysis was conducted for each outcome. Twenty-one RCTs and one observational study with 2277 participants were included. Results: Meta analysis indicated a benefit of ω-3 PUFAs on coronary atherosclerosis: 1. ω-3 PUFAs can reduce the atherosclerotic plaque volume (SMD, -0.18; 95%CI, −0.31 to-0.05); 2. ω-3 PUFAs can help reduce the loss of the diameter of the narrowest segments of coronary arteries in patients with CHD (SMD, 0.29; 95%Cl, 0.05 to 0.53); 3. ω-3 PUFAs don't have significant effect on volume of lipid plaque in coronary arteries (SMD, -1.18; 95%CI, −2.95 to 0.58), volume of fiber plaque (SMD, 0.26; 95%CI, −0.81; to 1.33) and calcified plaque (SMD, 0.17; 95%CI, -0.55 to 0.89); 4. ω-3 PUFAs had no significant effect on endothelial inflammatory factors in peripheral blood. Conclusions: We confirmed that ω-3 PUFAs benefit patients with coronary heart disease by reducing the progression of coronary atherosclerosis. And we indicated that the benefits were not caused by reducing endothelial inflammations of coronary arteries.